Lnc-CNNM3-DT as a protective factor in cervical cancer: regulation of LIAS expression and intracellular copper levels - Yang, Ying; Zhu, Xuehong; Sun, Dan; Fan, Jiangtao (Frontiers in Oncology, 2025)
BackgroundCervical cancer (CC) is the fourth leading cause of cancer-related death in women globally.While early screening has reduced mortality, tumor metastasis remains a significant concern, particularly in developing countries. Recent studies have identified cuproptosis, a copper-dependent cell death mechanism, as a potential factor in tumor progression. Long non-coding RNAs (lncRNAs) are key regulators of tumor progression. This study investigates the role of cuproptosis-related lncRNA (CRL) CNNM3-DT in CC, focusing on its impact on LIAS expression, intracellular copper levels, and tumor progression.MethodsWe analyzed the expression of lnc-CNNM3-DT and LIAS in clinical samples and CC cell lines using Real-time Polymerase Chain Reaction (RT-qPCR), Western blot, and immunohistochemistry (IHC). Functional assays, including CCK-8, wound healing, transwell invasion, and flow cytometry, were used to evaluate the effects of lnc-CNNM3-DT overexpression on cell proliferation, migration, invasion, and apoptosis. Intracellular copper ion levels were measured, and correlations between lnc-CNNM3-DT, LIAS, and clinicopathological features were analyzed.ResultsLnc-CNNM3-DT expression was significantly higher in paracancerous tissues and normal cervical epithelial cells compared to tumor tissues and CC cell lines. Overexpression of lnc-CNNM3-DT suppressed proliferation, migration, and invasion of HeLa and SiHa cells while enhancing apoptosis. Additionally, lnc-CNNM3-DT overexpression downregulated LIAS expression and decreased intracellular copper ion levels. Correlation analysis indicated that lnc-CNNM3-DT expression was negatively associated with tumor diameter and depth of invasion, while LIAS expression showed no significant correlation with clinicopathological features.ConclusionOur findings suggest that lnc-CNNM3-DT functions as a protective factor in CC by inhibiting tumor progression through downregulation of LIAS expression and reduction of intracellular copper levels. These results highlight lnc-CNNM3-DT as a potential biomarker and therapeutic target in CC.